English in the expanding circle : elements for a comparative study of the sociolinguistic profile of English in Turkey and Portugal - Erçin, Merve (2020)
This dissertation discusses the sociolinguistic profile of English in two Expanding Circle countries, Turkey and Portugal. The use of English in functional domains typically affected by English in such speech communities is assessed through the observation of its use in the media, the tourism sector and shop naming. The dissertation then examines the circumstances in which English is taught and learned in the subject countries, considering in particular the history and current status of English language teaching in each of them, the attitudes, especially of learners, towards the English language, and the levels of proficiency in English in both speech communities. Results from the investigation reveal that English is less present in Turkey than in Portugal within the domains of media and tourism, though its relevance in shop naming practices is similar in both countries. The teaching/learning circumstances of English are found to be quite different in the two speech communities, with the maintenance, in Turkey, of more traditional methodologies and less successful results, as proficiency indexes remain lower in Turkey than in Portugal. Attitudes to English prove to be favourable in Portugal and mixed in Turkey. The sociolinguistic profile of English and Turkey proves therefore to be different, though both countries are growingly dependent on English and not so distant members of its Expanding Circle.